School-aged children: a reservoir for continued circulation of Haemophilus influenzae Type b in the United Kingdom - Oh, S; Griffiths, D; John, T; Lee, Y; Yu, L; McCarthy, N; Heath, P; Crook, D; Ramsay, M; Moxon, E; Pollard, A (University of Chicago Press, 2008)
Background: A resurgence of Haemophilus influenzae type b (Hib) disease occurred in the United Kingdom between 1999 and 2003 and was partially attributed to lower immunogenicity of combination vaccines. The reservoir for Hib that led to transmission in this period is unknown. Methods: We estimated the point prevalence of Hib carriage in school-aged children and adults, using oropharyngeal swabbing and selective media. We characterized the Hib isolates by multilocus sequence typing (MLST) and measured Hib antibody concentrations in adults by enzyme-linked immunosorbent assay. Results: Point prevalence for Hib carriage in 855 children aged 6-16 years was 4.2% (95% confidence interval [CI], 2.5%-5.9%). Five clonal groups of Hib were identified by MLST, 86% from the lineage of sequence type 6. No Hib was isolated in 385 adults (upper limit of 95% CI, 0.95%). The geometric mean concentration of serum antibody to polyribosylribitol phosphate was 0.47 μg/mL (95% CI, 0.37-0.59 μg/mL) in adults. Conclusions: Hib carriage is common in school-aged children, who are a significant reservoir for ongoing transmission of Hib to susceptible individuals in the United Kingdom. Surveillance of transmission and immunity across all ages of the population is essential to monitor the evolution of Hib epidemiology.